2018
DOI: 10.1002/jhet.3234
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone–Triazole Hybrids and their Biological Activities

Abstract: Hybridization, a strategy based on the covalent fusion of two or more existing pharmacophores to create a single molecule with multiple mechanisms of action, represents an encourage approach in the development of new drugs with potential therapeutic application in several pathologies. Triazoles and quinolones occupy an important position in medicinal chemistry attribute to their various biological activities, so hybridization of these two pharmacophores may provide more effective candidates that might be able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 101 publications
2
27
0
1
Order By: Relevance
“…Fluoroquinolone antibiotics possess excellent efficiency for the treatment of various bacterial infections such as upper and lower respiratory infections, sexually transmitted diseases, soft tissue infections, and community‐acquired pneumonia, and play a pivotal role in the anti‐infective chemotherapy field. [ 28–30 ] Obviously, the hybridization of fluoroquinolone with isatin is a promising strategy in the development of new drugs with potential therapeutic efficacy. The isatin–ciprofloxacin–isatin hybrids 3 (MIC: 4 to >128 μg/ml) and isatin–gatifloxacin–isatin hybrids 4 (MIC: 16 to >64 μg/ml) showed weak to moderate activity against the tested eight Gram‐positive and 15 Gram‐negative strains, and the activity was far less potent than the parents ciprofloxacin (MIC: ≤0.03–64 μg/ml) and gatifloxacin (MIC: ≤0.03–32 μg/ml) against most of the tested pathogens, implying incorporation of the isatin dimers into fluoroquinolones was harmful to the antibacterial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoroquinolone antibiotics possess excellent efficiency for the treatment of various bacterial infections such as upper and lower respiratory infections, sexually transmitted diseases, soft tissue infections, and community‐acquired pneumonia, and play a pivotal role in the anti‐infective chemotherapy field. [ 28–30 ] Obviously, the hybridization of fluoroquinolone with isatin is a promising strategy in the development of new drugs with potential therapeutic efficacy. The isatin–ciprofloxacin–isatin hybrids 3 (MIC: 4 to >128 μg/ml) and isatin–gatifloxacin–isatin hybrids 4 (MIC: 16 to >64 μg/ml) showed weak to moderate activity against the tested eight Gram‐positive and 15 Gram‐negative strains, and the activity was far less potent than the parents ciprofloxacin (MIC: ≤0.03–64 μg/ml) and gatifloxacin (MIC: ≤0.03–32 μg/ml) against most of the tested pathogens, implying incorporation of the isatin dimers into fluoroquinolones was harmful to the antibacterial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…F I G U R E 2 Chemical structures of the N-1 position-tethered isatin dimers 1-4 with antibacterial activity Fluoroquinolone antibiotics possess excellent efficiency for the treatment of various bacterial infections such as upper and lower respiratory infections, sexually transmitted diseases, soft tissue infections, and community-acquired pneumonia, and play a pivotal role in the anti-infective chemotherapy field. [28][29][30] Obviously, the hybridization of fluoroquinolone with isatin is a promising strategy in the development of new drugs with potential therapeutic efficacy.…”
Section: F I G U R E 1 Chemical Structures Of Isatin and Indirubinmentioning
confidence: 99%
“…Quinolones which can be divided into 2‐quinolones and 4‐quinolones (Figure ) possess a variety of pharmacological properties such as antibacterial, anticancer, antitubercular, antimalarial, anti‐HIV and antifungal properties, and occupy an important place in the development of new drugs. Combined application of available antifungal drugs (such as fluconazole and amphotericin B) and quinolone antibiotics (such as trovafloxacin) has additive‐to‐synergistic activities over the use of antifungal drugs alone, suggesting that this may be a viable avenue to pursue the pending development of specific antifungal quinolones …”
Section: Introductionmentioning
confidence: 99%
“…The structure-activity relationship (SAR) demonstrated that the linker between the two isatin motifs influenced the biological activities significantly [15][16][17][18][19][20], so rationale design of the linker may provide more effective candidates. 1,2,3-Triazole motif can act as the isostere of amide, ester, carboxylic acid, and other heterocycles, and many drugs contain 1,2,3-triazole fragment [21][22][23]. Obviously, 1,2,3-triazole is an excellent linker.…”
Section: Introductionmentioning
confidence: 99%